Anion Exchange Solid-Phase Extraction Combined with High Performance Liquid Chromatography to Determine Bensulfuron Methyl in Wheat and Soil - Wu, M.; Hu*, J.Y. (Asian Journal of Chemistry, 2014)
A simple and reliable method based on solid-phase extraction with anion exchange column was developed for the determination of bensulfuron methyl residues in soil, wheat straw and grain by high performance liquid chromatography with an ultraviolet detector (HPLC-UV). The average recoveries were found ranged from 83.3 to 99.5 % with RSD values less than 6.85 %, at fortification levels of 0.01/0.05, 0.1 and 0.5 mg/kg. The validated method has been successfully applied to analyze the dissipation and residues of bensulfuron methyl in Beijing, Shandong and Anhui Provinces, China. The half-lives of bensulfuron methyl in soil and wheat straw from experimental field were 4.62-8.66 days and 2.39-4.05 days, respectively. The terminal residues of bensulfuron methyl in wheat grain were all below maximum residue level value set by China (0.02 mg/kg). The pesticide extracted from field sample was confirmed by liquid chromatography-mass spectrometry (LC-MS).